Partition of India: The Process of Othering and A Living Memory - Ahmad Bhat, Shabir; Ahmad, Ishfaq (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the Partition of India in 1947 and its enduring and unresolved legacies, which continue to impact contemporary South Asian geopolitics. It examines how Hindus and Muslims were divided along communal lines as a result of the British Raj’s “divide and rule” policy, which prepared the way for the Muslim League’s demand for a separate homeland based on the Two Nation Theory. The Paper makes the case that although Partition brought about freedom, it also led to one of the biggest forced migrations in history and unexpectedly high levels of sectarian bloodshed. Roughly a million people lost their lives in riots and massacres, during which women were the targets of rape, kidnappings, and honor killings carried out as a kind of warfare. The paper contends that Partition created several geostrategic tensions that remain flashpoints. The Kashmir dispute represents the ’unfinished business’ of Partition, while border demarcations defying river geography have led to enduring water disputes between India and Pakistan. Discrimination encountered by minorities left on the wrong side of the border highlights Partition’s inability to ease tensions between communities. The nuclearization of the India-Pakistan rivalry also demonstrates Partition’s toxic legacy. Thus, the unhealed wounds and unresolved problems born out of Partition continue to impact regional identities, politics, conflicts, and peacebuilding. The paper analyses Partition as an ongoing process, not just a singular historic event, providing insight into its contentious legacy that still has the potential to ignite conflict in contemporary South Asia.